The analysis of game theory in ethical decision-making - Farhan, Djuni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the application of Game Theory in ethical decision-making processes, employing a qualitative research method through literature review and library research. The primary objective is to analyze how Game Theory models, such as the Prisoner's Dilemma and Nash Equilibrium, can provide insights into the dynamics of ethical decisions within various social and organizational contexts. By reviewing existing literature, the study identifies key factors influencing ethical behavior, such as individual incentives, cooperation, and the impact of strategic interactions. The findings suggest that Game Theory provides a robust framework for understanding ethical dilemmas, particularly in situations where personal interests may conflict with collective well-being. Additionally, the research highlights the importance of considering long-term consequences and repeated interactions when applying Game Theory to ethics, as these elements can encourage cooperation and reduce unethical behavior. The study also acknowledges the limitations of Game Theory in fully capturing the complexity of moral and ethical considerations, as it is often grounded in rational choice theory, which may not account for emotional or cultural factors. Nevertheless, this research contributes to the broader understanding of how theoretical models can inform ethical decision-making and proposes further interdisciplinary studies to refine the integration of Game Theory into ethical frameworks.